The Assistive Technology for Teaching and Learning of Social Skills for Autism Spectrum Disorder Children: Multimedia Interactive Social Skills Module Application - Ibrahim, Zuraida; Mohamed, Juliana; Kassim, Noordiana; Bahrudin, Ida Aryanie (2023)
An earlier study found that assistive technology based on mobile applications significantly improved how social skills were taught to and learned by autism spectrum disorder (ASD) children. Nevertheless, the content of the existing mobile applications is inadequate for capturing the diversity of Malaysian culture, making it unacceptable for local use. Considering cultural norms is a factor in developing social skills in ASD children. It is therefore necessary to develop new assistive technology based on mobile applications that consider Malaysian cultural norms. As a result, the Multimedia Interactive Social Skills Module (MISSM) application was created based on the Addie Model, which offers a systematic process for assisting in developing successful instructional material by fusing instructional theory with learning theory. The MISSM application is based on Malaysia's current social skills curriculum, which helps ASD children become socially competent. Hopefully, it will help them develop better social skills and achieve academically. Finally, local culture-sensitive material for assistive technology based on mobile applications would support Malaysia's adoption of a technologybased teaching and learning strategy and contribute to a better understanding of social skills.